Primary lymphedema French National Diagnosis and Care Protocol (PNDS; Protocole National de Diagnostic et de Soins) - Stéphane Vignes (Orphanet Journal of Rare Diseases, 2021)
Abstract Primary lymphedema is a rare chronic pathology associated with constitutional abnormalities of the lymphatic system. The objective of this French National Diagnosis and Care Protocol (Protocole National de Diagnostic et de Soins; PNDS), based on a critical literature review and multidisciplinary expert consensus, is to provide health professionals with an explanation of the optimal management and care of patients with primary lymphedema. This PNDS, written by consultants at the French National Referral Center for Primary Lymphedema, was published in 2019 ( https://has-sante.fr/upload/docs/application/pdf/2019-02/pnds_lymphoedeme_primaire_final_has.pdf ). Primary lymphedema can be isolated or syndromic (whose manifestations are more complex with a group of symptoms) and mainly affects the lower limbs, or, much more rarely, upper limbs or external genitalia. Women are more frequently affected than men, preferentially young. The diagnosis is clinical, associating mild or non-pitting edema and skin thickening, as confirmed by the Stemmer’s sign (impossibility to pinch the skin on the dorsal side or the base of the second toe), which is pathognomonic of lymphedema. Limb lymphoscintigraphy is useful to confirm the diagnosis. Other causes of swelling or edema of the lower limbs must be ruled out, such as lipedema. The main acute lymphedema complication is cellulitis (erysipelas). Functional and psychological repercussions can be major, deteriorating the patient’s quality of life. Treatment aims to prevent those complications, reduce the volume with low-stretch bandages, then stabilize it over the long term by exercises and wearing a compression garment. Patient education (or parents of a child) is essential to improve observance.